2009
DOI: 10.1016/j.otohns.2009.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the Neurolaryngology Study Group on laryngeal electromyography

Abstract: The Neurolaryngology Study Group convened a multidisciplinary panel of experts in neuromuscular physiology, electromyography, physical medicine and rehabilitation, neurology, and laryngology to meet with interested members from the American Academy of Otolaryngology Head and Neck Surgery, the Neurolaryngology Subcommittee and the Neurolaryngology Study Group to address the use of laryngeal electromyography (LEMG) for electrodiagnosis of laryngeal disorders. The panel addressed the use of LEMG for: 1) diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 97 publications
3
70
1
10
Order By: Relevance
“…Similarly, a multidisciplinary panel convened by the Neurolaryngology Study Group of the American Academy of Otolaryngology-Head and Neck Surgery found that LEMG is most useful for predicting poor functional outcome and is clinically useful as a qualitative, rather than quantitative, measure. They concluded that further studies are needed to standardize the practice of LEMG and determine its optimum utility and clinical value [45].…”
Section: Laryngeal Electromyographymentioning
confidence: 99%
“…Similarly, a multidisciplinary panel convened by the Neurolaryngology Study Group of the American Academy of Otolaryngology-Head and Neck Surgery found that LEMG is most useful for predicting poor functional outcome and is clinically useful as a qualitative, rather than quantitative, measure. They concluded that further studies are needed to standardize the practice of LEMG and determine its optimum utility and clinical value [45].…”
Section: Laryngeal Electromyographymentioning
confidence: 99%
“…1 LEMG performed in the proper time frame can provide prognostic information regarding recovery after vocal fold paralysis. Although the literature offers only level IV evidence, the data clearly indicate that LEMG can accurately predict (75%-100%) which patients will not recover vocal fold motion (Table 3 in Sataloff et al 1 and reference 57 in Blitzer et al 2 ). A recent study from Pittsburg 3 added evaluation for synkinesis to the traditional signs indicating a poor prognosis for recovery, which increased their LEMG predictive value for ''no return of movement'' from 80% to 100% at their institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Among otolaryngologists that have interest in laryngological disorders, up to three quarters use LEMG clinically. 2 Despite commonly accepted practice, in 2004, an evidence-based review was not able to support the use of LEMG by available published research. 1 The topic was re-evaluated in 2006 by the Neurolaryngology Study Group of the American Academy of Otolaryngology Head and Neck Surgery with the conclusion that there is a role for LEMG in the diagnosis of vocal fold movement disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein lies the role of Laryngeal electromyography (LEMG), a procedure for recording the electrophysiological phenomena occurring in the intrinsic laryngeal muscles using various types of electrodes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%